Privatization of public space: stakeholder analysis in shifting the function of public space case study in Kediri city, Indonesia - Ningtyas, Trimurti; Amanah, Siti (Management and Entrepreneurship: Trends of Development, 2022)
Infrastructure development must take into account the needs and safety of the people living around the area where the infrastructure will be built. Kediri is one of the cities in East Java that has experienced rapid development in the last ten years. The government is the main actor because the policy on the management of public space is in government agencies. This study aims to determine the shift in the function of public space and how the interests that exist in it. Using descriptive qualitative methods with three data collection techniques, namely interviews, observations and documentation to informants consisting of the Department of Industry and Trade, the Department of Transportation, Street Vendors, and the general public. The result is a pattern of shifting the function of public space in the City of Kediri, consisting of three, namely the shift of the function of the sidewalk to a trading area, the shift of the function of the road to a parking area, the shift of the function of convenience to fulfillment of needs. In addition, there are three types of stakeholders that have been identified, namely key, primary and secondary.JEL Classification: R32, R53, R58